Extended-spectrum beta-laktamase (ESBL) enzyme producing bacteria isolated from rectal swabs of around animals in dairy farms - Dameanti, Fidi Nur Aini Eka Puji; F, Jacky T. Amanda; Safri, Muhammad Ali A.; Hasan, Chyntia S. Y. (Fakultas Peternakan Universitas Papua, 2024)
This study aims to identify bacterial contamination of Klebsiella pneumoniae and Escherichia coli producing Extended Spectrum Beta Lactamase (ESBL) isolated from rectal swabs of local animals on a dairy farm in Deyeng Village, Kediri, East Java. Interviews and observations were conducted with farmers to obtain the required risk factor data (cleanliness of drinking and eating places, drinking water sources, and administration of antibiotics to livestock). The number of samples tested in this study was 34 samples, including 12 chicken samples, 8 goat samples, 5 duck samples, 4 rabbit samples, 3 cat samples and 2 goose samples. Samples were isolated on MCA media + cefotaxime 1 mg/l and isolated again on MCA media without the addition of antibiotics to multiply pure bacterial colonies. The tests carried out to determine the presence of ESBL-producing bacteria are biochemical tests, namely the IMViC test (Indole, Methyl red, Voges-Proskauer, Citrate Utilization), TSIA (Triple Sugar Iron Agar) test, gram staining, and the Double Disk Standard Method test using β-lactam disc antibiotics, namely cefotaxime 30μg, ceftazidime 30μg, and amoxycilline-clavulanate acid 30μg. The results of this research were that 6 samples or 17.6% of ESBL-producing bacteria were identified from poultry groups (chickens, ducks and geese) from dairy farms in Deyeng Village, Kediri Regency, East Java.